Water biofilter system and biofilter media on pacamã larviculture - Pedreira, Marcelo Mattos; Luz, Ronald Kennedy; Santos, José Cláudio Epaminondas dos; Sampaio, Edson Vieira; Silva, Rafael Sá Fortes (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to investigate the use of different biofilter systems and biofilter media on water quality and performance of Lophiosilurus alexandri larvae. The treatments used were: no biofilter system (SB); internal biofilter with 1.6 cm average diameter shingle media (CMe); internal biofilter with 2.1 cm average diameter shingle media (CMa); a mix of 70% of grit (1.3 cm average diameter) and 30% of shell media (1.1 cm average diameter) (CB); and a closed recirculating system with external biofilter with 70% grit and 30% shell media (SF). The experiment was carried out in a completely randomized design, with five treatments and five replicates, during 16 days. Interaction between the rearing systems x rearing days affected the ammonium ion, nitrite, nitrate and orthophosphate concentrations. The SF, CMe and CB systems showed lower ammonium and nitrite concentrations; the SB system, higher ammonium ion concentrations and lower nitrate concentrations; the SF system, higher orthophosphate concentrations. L. alexandri survival was worst in the SF system. Fish growth was not affected by the different systems used. The biofilters provide better water quality in terms of nitrogenous waste depending on the biofilter media.